DNA Binding and Cleavage Activities of Na[B(Glu)(OH)2]·2H2O, Na[B(Cit)(OH)2]·2H2O, Li[B(Sal)(OH)2], and Mg[B(Sal)(OH)2]·2H2O Complexes. (9th December 2013) - Arslantas, A.; Devrim, A. K.; Sudagidan, M.; Köse, D. A.
Abstract : The interaction of some previously reported complexes Na[B(Glu)(OH)2 ]·2H2 O, Na[B(Cit)(OH)2 ]·2H2 O, Li[B(Sal)(OH)2 ], and Mg[B(Sal)(OH)2 ]·2H2 O with cattle genomic DNA (CG-DNA) was investigated using UV absorption, viscosity measurements, and fluorescence studies. These complexes interact with DNA through the intercalative mode of binding. In addition, the DNA cleavage activity of the complexes in presence of H2 O2 was determined using agarose gel electrophoresis. All complexes exhibit moderate ability of cleavage to the DNA.